Experiences of new diagnoses among HIV-positive persons: implications for public health - Adobea Yaa Owusu (BMC, 2022)
Abstract Background Ready acceptance of experiences of new diagnoses among HIV-positive persons is a known personal and public health safety-net. Its beneficial effects include prompt commencement and sustenance of HIV-positive treatment and care, better management of transmission risk, and disclosure of the HIV-positive status to significant others. Yet, no known study has explored this topic in Ghana; despite Ghana's generalised HIV/AIDS infection rate. Existing studies have illuminated the effects of such reactions on affected significant others; not the infected. Methods This paper studied qualitatively the experiences of new diagnoses among 26 persons living with HIV/AIDS. Sample selection was random, from two hospitals in a district in Ghana heavily affected by HIV/AIDS. The paper applied the Hopelessness Theory of Depression. Results As expected, the vast majority of respondents experienced the new diagnoses of their HIV-positive infection with a myriad of negative psychosocial reactions, including thoughts of committing suicide. Yet, few of them received the news with resignation. For the vast majority of respondents, having comorbidities from AIDS prior to the diagnosis primarily shaped their initial reactions to their diagnosis. The respondents' transitioning to self-acceptance of their HIV-positive status was mostly facilitated by receiving counselling from healthcare workers. Conclusions Although the new HIV-positive diagnosis was immobilising to most respondents, the trauma faded, paving the way for beneficial public health actions. The results imply the critical need for continuous education on HIV/AIDS by public health advocates, using mass media, particularly, TV. Healthcare workers in VCTs should empathise with persons who experience new diagnoses of their HIV-positive status.